Diversity and Abundance of Birds in Coastal Habitats of Tanjung Datu National Park and Samunsam Wildlife Sanctuary, Sarawak - Ng, Wen Teng; Mohamad Fizl Sidq, Ramji; Hilda Jelembai, Neilson Ilan; Nur Nadhirah Izzaty, Selamat; Siti Noorzaimira, Mohd Zaini (UNIMAS Publisher, 2024)
A series of bird survey was conducted in three separate sampling occasions from September 2018 to January 2019 at Tanjung Datu National Park and Samunsam Wildlife Sanctuary, Sarawak, with an accumulation of 2440 net hours. The objective of this survey was to determine the species diversity and abundance of birds in coastal habitats of these protected areas. The survey utilised two primary methods: mist-netting and visual-aural detection on boat-cruise covering six predetermined routes (ca. 1 km each) along the coastal shorelines. Additionally, the opportunistic observation was also conducted along the coastal beach. Twenty mist nets were deployed and left open for 12 hours (0700-1900 hr) for eleven days with a total of 2640 net/hours. Whilst, boatcruises were conducted twice daily: during the morning (0800-1000 hr) and late afternoon session (1600-1800 hr). Overall, a total of 93 bird species from 40 families were recorded throughout the surveys. Of these, 89% were residents (including one resident endemic) and 11% were migrants (including Plovers, Sandpipers, Whimbrel, Stint, Pacific Swallow, Arctic Warbler and Brown Hawk-owl). Our mist-netting effort yielded 128 individuals representing 39 species from 21 families. The most abundant species was the Little Spiderhunter (Arachnothera longirostra) with 20 individuals, followed by 17 individuals of Olive-winged Bulbul (Pycnonotus plumosus). From this survey, a total of 32 species were listed in Appendices I (6 Totally Protected species) and Appendices II (26 Protected species) of the Sarawak Wildlife Protection Ordinance (SWPO, 1998). Several notable records include the Black Hornbill (Anthracoceros malayanus), Bushy-crested Hornbill (Anorrhinus galeritus), Great Argus (Argusianus argus), Great Slaty Woodpecker (Mulleripicus pulverulentus) and the rare Malaysian Honeyguide (Indicator archipelagicus). The high diversity of birds in coastal mangroves, mudflat, and sandy beaches further highlights the importance of conserving habitat heterogeneity from anthropogenic disturbance and forest degradation.